KORELASI KEPADATAN LALU LINTAS TERHADAP KADAR NITROGEN DIOKSIDA DAN KLOROFIL TALUS LIKEN PADA TEGAKAN POHON ANGSANA (Pterocarpus indicus) DI KAWASAN INDUSTRI MEDAN 2 - Nainggolan, Tiara Bunga; Hasairin, Ashar (Universitas Jambi, 2025)
Industrial areas are centers of economic activity that contribute significantly to air pollution, particularly Nitrogen Dioxide (NO₂). This research aimed to explore the relationship between traffic density, NO₂ levels, and chlorophyll content in lichen thalli on Angsana trees (Pterocarpus indicus) in Medan Industrial Area 2. This quantitative descriptive study was conducted over three months, with lichen samples collected using purposive sampling method at two locations with different traffic densities. Data collection included measurements of traffic density, environmental parameters, lichen identification, NO₂ level analysis, and chlorophyll content measurement. The results showed a very strong positive correlation between traffic density and NO₂ levels in lichen thalli, and a strong negative correlation between traffic density and total chlorophyll content. A significant negative correlation was also found between NO₂ levels and total chlorophyll content in lichen thalli. Six lichen species from five families with two different thallus types were identified on Angsana trees, showing variations in coverage area and physiological responses to pollution levels. This study concludes that lichens are effective bioindicators for detecting NO₂ pollution in industrial areas with varying traffic densities.